Mempertanyakan Pancasila Sebagai Grundnorm: Suatu Refleksi Kritis Dalam Perspektif Fondasionalisme - Manullang, E. Fernando M. (UI Scholars Hub, 2020)
Legal scholars in Indonesia discuss whether Pancasila is grundnorm or not. Grundnorm according to Hans Kelsen is the basis for validity of legal norms. Kelsen is therefore considered a foundational scholar according to Luc J. Wintgens. Meanwhile, in the view of foundationalism, certain foundation can be accepted if such foundation becomes belief. Thus, saying that Pancasila is basic norm or not, in the view of foundationalism shall answer whether Pancasila is a belief or not. Instead of continuing the debates whether Pancasila is a grundnorm or not, this article instead takes the pre-debates stands, namely reflecting critically the question Pancasila is a grundnorm or not, as unreasonable based on a foundationalism philosophy. For Kelsen, grundnorm is merely source of validity. Kelsen rejected grundnorm containing belief, which psychological in nature, an alien element to the law. While Pancasila is philosophical value, a belief which cannot be reduced only to the validity.